FRI0003 Modulation of articular joint tissue turnover in bovine explant models of cartilage and synovial membrane: development of novel drug development tools. (15th June 2017) - Siebuhr, AS; Cabanes, CA; Dahab, S; Karsdal, MA; Bay-Jensen, A-C; Thudium, CS
Abstract : Background: There is currently a lack of disease modifying OA drugs approved by the drug administration agencies. One of the obstacles in the development of DMOADs that can effectively halt or reverse cartilage degradation is the lack of robust and reproducible model systems for early drug testing. Objectives: To develop inducable anabolic bovine ex vivo models of 1) synovial membrane explants and 2) synovial membrane explants in co-culture with cartilage explants. Methods: Synovium (bSME) from healthy bovine (<24months old) hind knees were isolated and cut into explants of 30±5 mg. Bovine cartilage (BEX) was cut into equally sized explants using a 6mm diameter biopsy puncher. bSME and BEX were cultured together (bCC) or alone for 14–35 days in DMEM-GlutaMAX™ with or without continuous stimuli in 4 replicates per treatment: Oncostatin M [10 ng/mL] + TNF-α [20 ng/mL] (O+T), O+T + GM6001 [1uM], IGF-1 [100ng/mL] or TGFβ-1 [50–0.5 ng/mL]. Media were changed 3 times a week and the viability was assessed with Alamar Blue every week. The reversibility of synovial membrane degradation was investigated by 10 days incubation with O+T followed by 21 days of TGFβ-1 [50–0.5 ng/mL] treatment. The following biomarkers were assessed in the conditioned media by competitive ELISA: Type I, II and III collagen degradation (C1M, C2M and C3M), formation of type I and II collagen (P1NP and PRO-C2), aggrecanase degraded aggrecan (AGNxI) and MMP degraded aggrecan (exFFGV). C1M and C3M are synovial membrane biomarkers and C2M, AGNxI and exFFGV are cartilage biomarkers. Results: Explants were viable throughout the experiments, albeit the bSME lost some viability with time. bSME treated with O+T showed increased C1M and C3M (>400% and >200%) from day 10, compared to w/o, whereas in bCC O+T increased C1M from day 21 and C3M from day 14 (>800%, >1900%). O+T treatment increased C2M was increased from day 21 (>400% and >1000%) in both BEX and bCC. The release was blocked by the generic MMP inhibitor GM6001 which also decreased the C1M and C3M compared to w/o. O+T treatment increased AGNxI at day 7 and 10 (>600%) and exFFGV from day 21 (>650%) in both BEX and bCC. In bSME, TGF-b1 continuously and dose-dependently increased P1NP from day 7 compared to w/o (250%). O+T pre-treatment for 10 days followed by TGF-b1 stimulation increased P1NP after 7 days of TNF-b1 treatment (150%, figure). IGF-1 did not affect the P1NP level at any time point in bSME. In bCC both TGF-b1 (dose-dependently) and IGF-1 sustained the PRO-C2 level at the level of baseline throughout the study periods (figure), whereas O+T decreased PRO-C2 compared to with w/o. The PRO-C2 level in BEX with TGF-b1 was unaltered compared to w/o. Conclusions: We here show that bovine synovium can be anaobolic and catabolic stimulated, both alone and in co-culture with cartilage. Anabolic stimulation was achieved with TGF-b1 in both bSME and bCC, while IGF-1 only showed an anabolic effect in the bCC. Previous human explant models using human tissuehave lacked the anabolic capacity. These translational explants models may be applied in the early development of anabolic drugs for cartilage degenerative diseases. Disclosure of Interest: A. S. Siebuhr Employee of: Nordic Bioscience, C. Cabanes: None declared, S. Dahab: None declared, M. Karsdal Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, A.-C. Bay-Jensen Employee of: Nordic Bioscience, C. Thudium Employee of: Nordic Bioscience